Non‐invasive structure–function assessment of the liver by 2D time‐harmonic elastography and the dynamic Liver MAximum capacity (LiMAx) test. Issue 9 (10th March 2019) - Heucke, Niklas; Wuensch, Tilo; Mohr, Julia; Kaffarnik, Magnus; Arsenic, Ruza; Sinn, Bruno; Müller, Tobias; Pratschke, Johann; Stockmann, Martin; Sack, Ingolf; Tzschätzsch, Heiko
Abstract: Background and Aim: Accurate assessment of structural and functional characteristics of the liver could improve the diagnosis and the clinical management of patients with chronic liver diseases. However, the structure–function relationship in the progression of chronic liver disease remains elusive. The aim of this study is the combined measurement of liver function by the 13 C‐methacetin Liver MAximum capacity (LiMAx) test and tissue‐structure related stiffness by 2D time‐harmonic elastography for the assessment of liver disease progression. Methods: LiMAx test and time‐harmonic elastography were applied, and the serological scores fibrosis 4 index and aspartate aminotransferase to platelet ratio index were calculated in patients with chronic liver diseases ( n = 75) and healthy control subjects ( n = 22). In 47 patients who underwent surgery, fibrosis was graded by histological examination of the resected liver tissue. Results: LiMAx values correlated negatively with liver stiffness ( r = −0.747), aminotransferase to platelet ratio index ( r = −0.604), and fibrosis 4 ( r = −0.573). Median (interquartile range) LiMAx values decreased with fibrosis progression from 395 μg/kg/h (371–460 μg/kg/h) in participants with no fibrosis to 173 μg/kg/h (126–309 μg/kg/h) in patients with severe fibrosis. Median liver stiffness increased progressively with the stage of fibrosis from no fibrosis (1.56 m/s [1.52–1.63 m/s]) to moderate fibrosis (1.60 m/s [1.54–1.67 m/s]) to severe fibrosis (1.85 m/s [1.76–1.92 m/s]). Conclusion: Our findings show that structural changes in the liver due to progressing liver diseases and reflected by increased tissue stiffness correlate with a functional decline of the organ as reflected by a decreased metabolic capacity of the liver.